Benchmarking the In Vitro Activities of Moxifloxacin and Comparator Agents against Recent Respiratory Isolates from 377 Medical Centers throughout the United States - Jones, Mark E. (American Society for Microbiology, 2000)
To benchmark the activity of moxifloxacin (a newer fluoroquinolone), a U.S. study comprising 16,141 contemporary isolates of Streptococcus pneumoniae (5,640), Haemophilus influenzae (6,583), and Moraxella catarrhalis (3,648) referred from 377 institutions during 1998 is described. For S. pneumoniae the modal MIC and MIC at which 90% of the isolates were inhibited (MIC(90)) for moxifloxacin were 0.12 and 0.25 μg/ml, respectively, independent of susceptibility to other drug classes, geography, or site of infection. Eleven isolates were intermediate or resistant to levofloxacin and grepafloxacin; of these isolates, 1 remained susceptible to sparfloxacin, 2 remained susceptible to moxifloxacin, and 4 remained susceptible to trovafloxacin. All 11 isolates possessed classic mutations in gyrA and/or parC known to confer reduced susceptibility to fluoroquinolones. Four isolates (originating from four separate states) belonging to a multidrug-resistant, fluoroquinolone-resistant clone were identified by pulsed-field gel electrophoresis. For moxifloxacin and trovafloxacin, at least 87% of isolates demonstrated MICs ≥3 twofold concentrations below the susceptibility breakpoints, in contrast to no more than 15% for levofloxacin, grepafloxacin, and sparfloxacin. Of the isolates that were multidrug resistant (7.4%), >98% remained susceptible to moxifloxacin. The modal MIC and MIC(90) for M. catarrhalis (both 0.06 μg/ml) and for H. influenzae (both 0.03 μg/ml) were independent of β-lactamase production. These data demonstrate the in vitro activity of moxifloxacin and establish a baseline for future studies.